STATISTICAL PROCESS CONTROL IN THE ASSESSMENT OF DRIP IRRIGATION USING WASTEWATER - F. de F. e Silva, Ênio (2018)
The aim of this study was to evaluate drip irrigation as a process, by monitoring the average flow applied by the emitter using tools of statistical quality control. Four kinds of drippers were selected, two inline labyrinth type and two online where one of the inline emitters was not self-compensating and the other, self-compensating emitter. The system was installed in the field and tested for 85 hours, using three kinds of treated domestic sewage effluents and tap water. The system was under statistical control when the emitters were new, however none of the drippers reaches the manufacturer's specification for average flow. The online drippers showed more dispersion for individual flow measurements and the non-self-compensating inline dripper was more accurately for this variable. After the end of experiment, irrigation process was not under statistical control for any kind of emitter. When using treated wastewater effluents for irrigation we recommend a first evaluation before 7 working hours, to implement appropriated correcting procedures to reduce clogging and as a result, maintain the process quality.